The Urgency of Regulating Witness Rights Accompanied by Legal Counsel in Pre-Adjudication Examination as a Form of Human Rights Fulfillment - Kadek Angga Dwipayana Putra; Sagung Putri M.E. Purwani (Transpublika Publisher, 2025)
The existing issue in the legal system is the lack of assurance and fairness in ensuring a witness's right to have legal representation during the pre-trial phase. The goal of this research is to evaluate the urgency of regulating the rights of witnesses accompanied by legal advisors during pre-trial examinations as a form of fulfilling human rights, as well as efforts to fulfill the rights of witnesses accompanied by legal advisors at the pre-adjudication stage as a form of fulfilling human rights. The benefits of writing provide a basic understanding regarding the urgency of regulating the rights of witnesses accompanied by legal advisors at the pre-trial stage as a form of fulfilling human rights. The emptiness of norms underlies this research with a type of normative legal research as well as a statutory and conceptual approach. The research results show that the urgency of regulating the rights of witnesses accompanied by legal advisors at the pre-trial stage is based on the principle of equality before the law which is fundamentally regulated in the constitution. In connection with efforts to fulfill the rights of witnesses accompanied by legal advisors at the pre-trial stage, extensive legal interpretation can be carried out by expanding the meaning of the definition of witness, so that the rights of witnesses described in the law can become a reference, in addition there is a role for law enforcers to assist in fulfilling the rights of witnesses.